The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.7566/jpsj.84.034711
|View full text |Cite
|
Sign up to set email alerts
|

Topological s-Wave Pairing Superconductivity with Spatial Inhomogeneity: Midgap-State Appearance and Robustness of Superconductivity

Abstract: We study the quasiparticle spectrum of 2D topological s-wave superconductors with the Zeeman magnetic field and the Rashba spin-orbit coupling in the presence of spatial inhomogeneity. Solving the real-space Bogoliubov-de Gennes equations, we focus on the excitations within the superconducting gap amplitude, i.e., the appearance of mid-gap states. Two kinds of potential functions, line-type (a chain of impurities) and point-type (a single impurity) ones are examined to take spatial inhomogeneity into account. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 35 publications
2
14
0
Order By: Relevance
“…For large α, even in the topological phase, L z /N does not reach −1/2, which is the intrinsic value in chiral p-wave SCs. We have explained the impurity effects on the topological SC: the appearance of the midgap bound states 31,33 , the reduction of the critical temperature 32 , and the vorticity dependence of the vortex bound state 34 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For large α, even in the topological phase, L z /N does not reach −1/2, which is the intrinsic value in chiral p-wave SCs. We have explained the impurity effects on the topological SC: the appearance of the midgap bound states 31,33 , the reduction of the critical temperature 32 , and the vorticity dependence of the vortex bound state 34 .…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to the Chern number which characterizes a topological SC, the bulk orbital AM may characterize how close it is to a spinless chiral SC with the same Chern number and how fragile it is to nonmagnetic impurities. Topological SCs are not always robust against nonmagnetic impurities, namely, the midgap bound states appear and the critical temperature T c is suppressed [31][32][33] . These impurity effects in the Rashba+Zeeman+s-wave model depend on h and are similar to those in a chiral p-wave SC for large h.…”
Section: Introductionmentioning
confidence: 99%
“…For example, in the study of topological superconductivity the interest usually lies in the detection of Majorana zero modes and the surrounding lowest-energy eigenvalues. For these reasons, the SS method is an excellent tool in the study of superconductivity as demonstrated by Nagai et al [50,70] and has proven to be extremely useful for the research presented in this thesis.…”
Section: The Sakurai-sugiura (Ss) Methodsmentioning
confidence: 96%
“…Within this model, we perform microscopic mean-field calculations and self-consistently obtain converged solutions for both the superconducting order parameter and the Hartree potential. The tight-binding Hamiltonian for such an s-wave topological superconductor is given by [70] …”
Section: Topological S-wave Superconductivity In Two Dimensionsmentioning
confidence: 99%
See 1 more Smart Citation